Production of transgenic first filial puppies expressing mutated human amyloid precursor protein gene - Hossein, Mohammad Shamim; Son, Young-Bum; Jeong, Yeon Woo; Jeong, Yeon Ik; Kang, Mi Na; Choi, Eun Ji; Park, Kang Bae; Bae, Yu Ra; Kim, Dae Young; Hwang, Woo Suk (Frontiers in Veterinary Science, 2023)
Propagation of transgenic animals by germline transmission using assisted reproductive technologies such as in vitro fertilization (IVF) is the most efficient way to produce transgenic colonies for biomedical research. The objective of this study was to generate transgenic puppies from a founder dog expressing the mutated human amyloid precursor protein (mhAPP) gene. Experiment I assessed the characteristics of the semen prepared by freshly diluted, swim-up, and Percoll gradient methods using a computer-assisted semen analyzer (CASA). Motile and progressively motile sperm counts were higher in the Percoll gradient samples (p < 0.05) than in the swim-up and freshly diluted samples. In Experiment II, a total of 59, 70, and 65 presumptive zygotes produced by fresh, Percoll gradient, and swim-up methods, respectively, were transferred to surrogates (5 for each group); the Percoll gradient (27.27%) and swim-up samples (14.29%) showed the highest blastocyst formation rates, while fresh diluted semen did not produce any blastocyst. Experiment III examined the full-term developmental ability of embryos. Among the 5 surrogates in the Percoll gradient group, one (20.0%) became pregnant; it had 4 (6.15%) sacs and delivered 4 (6.15%; 2 males and 2 females) live puppies. Among the 4 puppies, 2 (50.0%) were found to transmit the transgene on their nail and toe under GFP fluorescence. Furthermore, the integration and expression of the mhAPP transgene were examined in the umbilical cords of all the IVF-derived puppies, and the presence of the transgene was only observed in the GFP-positive puppies. Thus, semen prepared by the Percoll method could generate transgenic puppies by male germline transmission using the IVF technique. Our result will help propagate transgenic dogs efficiently, which will foster human biomedical research.